FRI0307 An outcome survey of 100 patients with cerebral venous sinus thrombosis due to behÇet's syndrome followed up at a single, dedicated center. (15th June 2017) - Kurt, EA; Ozguler, Y; Kocer, N; Ucar, D; Uygunoglu, U; Islak, C; Ugurlu, S; Hatemi, G; Saip, S; Melikoglu, M; Fresko, I; Hamuryudan, V; et al.
Abstract : Background: Behcet's syndrome (BS) is a well-recognized cause of cerebral venous sinus thrombosis (CVST). Objectives: We aimed to assess the outcome of a large cohort of patients with CVST due to BS attending a single dedicated center. Methods: We identified 100 (81 M/19 F) patients with BS who were diagnosed as having CVST. All contacted were called back to the outpatient clinic for clinical and imaging re-evaluation. Results: The mean age of the patients at the onset of the symptoms was 28±10 years. A total of 48 patients developed CVST before or at the onset of ISG fulfillment, while 52 developed CVST after a median 3 [2–8] years of ISG fulfillment. Superior sagittal (n=47) and transverse sinuses (n=46) were most commonly involved followed by sigmoid sinus (n=26) and jugular vein thrombosis (n=15). A total of 59 (53 M/ 6 F) patients had vascular involvement in addition to CVST: these were deep vein thrombosis of the lower extremities (n=47), pulmonary artery involvement (n=17), Budd-Chiari syndrome (n=9), vena cava superior thrombosis (n=6) and major arterial disease (n=3). In about half (32/59), CVST preceded any type of additional vascular involvement. Eye involvement was seen in 37, parenchymal CNS involvement in 8 (all later than CVST) and gastrointestinal involvement in 5 patients. Seven patients had died. By the end of the study, 87 patients were alive and contacted with a median follow-up time of 11 [6–15] years. Only 6 patients had a relapsing CVST course. Information about medical treatment was present in detail in 87 patients of whom 75 received short courses of glucocorticoids with (n=12) or without anti-coagulants. A total of 81 patients received immunosuppressive agents, most commonly azathioprine. Four patients underwent lumbo-peritoneal shunting surgery (1 was successful) and 1 with arterio-venous fistula underwent vascular embolization. Fifty patients were re-evaluated at the clinic. None had of symptoms of intracranial hypertension. Ophthalmological examination showed that 17 patients had complications such as bilateral optic atrophy (n=3), bilateral papilledema (n=5), bilateral optic disc pallor (n=4) and fibrotic scars around optic disc (n=5). Sensorineural type hearing loss was detected in 4 patients. Neurological examination was found to be normal in 43 patients with isolated CSVT, whereas abnormal in the remaining 7 patients with concomitant parenchymal CNS involvement. Cranial MR/MR venographies at the end of follow-up, were abnormal in 36 patients showing occlusion/ irregularity/ hypoplasia or collaterals in the sagittal (n=19) or transverse sinus (n=17). In the remaining 14, MR venographies were normal. Conclusions: CVST due to BS is closely associated with vascular involvement in the body and may be considered as a risk factor for future vascular involvement. CVST relapses are rare; however, the course is not uneventful: visual acuity or field may be impaired totally or partially because of optic disc atrophy; in addition hearing deficits may occur. Disclosure of Interest: None declared